ESTETIKA RESEPSI DAN INTERTEKSTUALITAS: PERSPEKTIF ILMU SASTRA TERHADAP TAFSIR AL-QUR’AN - Otong Sulaeman (Tanzil: Jurnal Studi Al-Quran, 2015)
The Quranic interpretation is an effort to explain the meaning of the Quranic verses. In literary studies, the Quranic interpretative attempt is an interpreter’s reception aestethics towards the Quranic verses. In another side, the interpreter (mufasir) is, during his effort of interpreting the Quran, necessarly influenced by the other texts he or she has ever read. The process of the interpreter’s being influenced by the other texts while interpreting the Quran is, in the literary theory, called intertextuality. Thus, there is a very close relation between the Quranic interpretation and literary sciences.